2008
DOI: 10.1097/qad.0b013e328307a051
|View full text |Cite
|
Sign up to set email alerts
|

Baseline renal insufficiency and risk of death among HIV-infected adults on antiretroviral therapy in Lusaka, Zambia

Abstract: Objective To examine the association between baseline renal insufficiency and mortality among adults initiating antiretroviral therapy (ART) in urban African setting. Design Open cohort evaluation Methods We examined mortality according to baseline renal function among adults initiating ART in Lusaka, Zambia. Renal function was assessed by the Cockcroft-Gault method, the Modification of Diet in Renal Disease (MDRD) equation, and serum creatinine. Results From April 2004 to September 2007, 25,779 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
98
8
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 32 publications
13
98
8
2
Order By: Relevance
“…The prevalence found in this study agrees to similar studies done around the world ranging from 3.6% to 42% [9,12,21,22]. The risk factors for renal dysfunction that we found in this population are consistent with previous findings, for example, in the adult population at University Teaching Hospital, Zambia [9,10] which suggested that CD4+ cell counts is an important risk factor.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The prevalence found in this study agrees to similar studies done around the world ranging from 3.6% to 42% [9,12,21,22]. The risk factors for renal dysfunction that we found in this population are consistent with previous findings, for example, in the adult population at University Teaching Hospital, Zambia [9,10] which suggested that CD4+ cell counts is an important risk factor.…”
Section: Discussionsupporting
confidence: 93%
“…The risk factors for renal dysfunction that we found in this population are consistent with previous findings, for example, in the adult population at University Teaching Hospital, Zambia [9,10] which suggested that CD4+ cell counts is an important risk factor. Other studies have suggested an association between CD4+ cell count of less than 200 cells/uL and renal dysfunction among patients exposed to TDF [6,9,23]. In this study, the median CD4+ cell count was 243.9 cells/ uL for those with CrCl>50ml/uL eliminating the assumption that renal dysfunction in this group could have been due to advanced HIV infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A study in Lusaka demonstrated that even mild (GFR 60 -89 ml/min) baseline renal insufficiency was associated with increased mortality after ART initiation. 13 This is important, as tenofovir is now part of the first-line HIV treatment regimen in South Africa. Screening for renal insufficiency is recommended before initiating ART, and patients with renal impairment must be followed up regularly.…”
Section: Discussionmentioning
confidence: 99%